Consciousness and Awareness: Quality Drive Initiative (QDI) Program in Punjab, Pakistan - Ul Kashif, Najam; Javed, Muhammad Latif; Jahan, Musarrat; Bahoo, Rabia (Pakistan Journal of Humanities and Social Sciences, 2022)
Quality drive initiative (QDI) was taken by Primary School Education Department of Punjab in order to develop the quality standards for the students of class one, two and three who were continuously being ignored by teachers. Owing to it the base of the students was very week which could not be covered till advanced class. In a survey conducted by CM ROAD MAP TEAM in 2021, it was observed that only 38% students were capable to recognize the things with words. Students of class one, two and three did not know how to read and write. Even they were unable to write their own names and match the things with words. So for making this initiative better this decision was taken to improve the standards of education for quality of early childhood education. Agenda of this program was to improve reading, writing, phonological and comprehension skills in Urdu and English and numeracy skills in mathematics. Guidelines were established for District Teacher Educators (DTEs) and Assistant Education Officers (AEOs) to provide guidance to teachers in fields for the improvements of results and to teach the students in natural and friendly environment. According to this initiative basic focus was given on three subjects English, Urdu and mathematics. Study aimed at what is the Quality Drive Initiative (QDI) and how they are improving the performance of primary students, in order to check the effectiveness of the program. To find out the perceptions of teachers on quality drive initiative program a questionnaire set for teachers, AEOs & DTEs. A test was also conducted before starting the QDI program. Results of the tests and response of the respondents show that QDI program meets its 80% target. For rural areas, this program shows better results as compared to urban areas. Interesting suggestions were made based on the findings.```